Thermoplasmonics: Molecular Hyperthermia: Spatiotemporal Protein Unfolding and Inactivation by Nanosecond Plasmonic Heating (Small 36/2017). Issue 36 (21st September 2017) - Kang, Peiyuan; Chen, Zhuo; Nielsen, Steven O.; Hoyt, Kenneth; D'Arcy, Sheena; Gassensmith, Jeremiah J.; Qin, Zhenpeng
Abstract : In article number 1700841, Zhenpeng Qin and co‐workers develop a novel method to create highly specific therapies by inactivating dysfunctional protein molecules. The approach inactivates protein molecules of interest by using short laser pulses and nanoparticles. This is achieved by nanosecond plasmonic heating of gold nanoparticles which creates an ultrahigh and ultrashort temperature increase, leading to selective inactivation and unfolding of proteins adjacent to the nanoparticle.